The Analysis of EEG Distribution for Human Brainwave due to Mobile Phone Usage. Issue 1 (September 2020) - Fuad, N.; Rahim, A.A.; Marwan, M.E.; Helmy Abd Wahab, Mohd; Zulkarnain Syed Idrus, Syed
Abstract: Brain is the most amazing thing that god create, without brain humans are just like living zombies. Brain generate electrical impulse that create brainwave. Therefore, from the brainwave there are four type of spectrum which are Delta, Theta, Alpha and Beta. Each spectrum has their own special meaning. For instance, there will be slight change in the brainwave pattern if that person answers a phone call. With the references of previous research, there is radiation in mobile phone that can cause headache. This headache can occur during the phone call. Thus, an experiment based on the different type of phone is conducted. In this research project, the different pattern of brainwave between answering phone call through GSM phone and smartphone are needed. This is to find out which phone give more radiation to the user. This experiment will take placed at one of the laboratories in the Faculty of Electrical and Electronic Engineering. Other than that, 20 subjects are needed for this experiment. The first step of this experiment is to collect data using EMOTIV Insight equipment. Next, the data is process in the SPSS and then, it will transfer to Microsoft Excel for better understanding of the result. In addition, the result obtain from this research project is that GSM phone cause more effect to the subject rather than smartphone. This is why nowadays, most of the people use smartphone compared to GSM phone. This because smartphone is user friendly and have less radiation.